2016
DOI: 10.9734/bjmmr/2016/25711
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Iron Deficiency Anemia among Chronic Kidney Disease Patients in Kaveri Delta Region, Tamilnadu, India

Abstract: Background: Iron deficiency anemia (IDA) is the most common type of anemia. But the incidence of iron deficiency anemia in chronic kidney disease (CKD) has not been well established in Kaveri Delta Region, Tamilnadu, India. Hence, the present study has been undertaken to evaluate the prevalence of iron deficiency anemia in chronic kidney disease patients of Kaveri Delta Region,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Our study revealed that iron deficiency anemia was present in nearly half (47.65%) of the patients with anemia. This is higher than the results reported in other studies, 39% in India, [ 11 ] 36.3% in Spain, and Catalonia. [ 22 ] Overall, the treatment of patients with anemia in this study was suboptimal.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Our study revealed that iron deficiency anemia was present in nearly half (47.65%) of the patients with anemia. This is higher than the results reported in other studies, 39% in India, [ 11 ] 36.3% in Spain, and Catalonia. [ 22 ] Overall, the treatment of patients with anemia in this study was suboptimal.…”
Section: Discussioncontrasting
confidence: 76%
“…[ 17 ] This result is also higher than the 43.18% reported in a study conducted in South Africa [ 13 ] and the 39.36% in India. [ 11 ] The variation with these studies might be due to differences in the study population that is, the inclusion of patients with advanced stages of CKD that is, stage 3 and above in our study, the study setting (single vs multi-center), and the number of patients included in these studies. Moreover, the high prevalence of anemia demonstrated in this study may be due to the high number of patients with advanced stage CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After approval from the institutional ethics review committee, the sample size was calculated using OpenEpi calculator 16 with 95% confidence interval (CI), exposed-tonon-exposed ratio of 1:1, 80% power and relative risks 2.5. It was assumed that 39% patients with CKD-ND have IDA 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Large differences have been reported on the magnitude of anemia in patients with CKD across studies. For instance, reports showed an anemia prevalence of 47.7% in the USA ( 9 ), 39.36% in India ( 10 ), 97.8% in Brazil ( 11 ), 51.5% in China ( 12 ), 79% in Cameroon ( 13 ), 43.18% in South Africa ( 14 ), and 64.5% in Ethiopia ( 15 ). In addition, African Americans had a 3-fold increased likelihood of anemia compared with whites ( 16 ).…”
Section: Introductionmentioning
confidence: 99%